2007
DOI: 10.1103/physrevlett.99.168001
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity Percolation in Particle-Laden Foams

Abstract: We study the viscoelastic behavior of aqueous foam mixed with solid noncolloidal particles. We show that adding a tiny amount of grains can enhance the elastic and loss shear moduli by more than 1 order of magnitude. The scaling of these moduli with solid volume fraction is in qualitative agreement with that predicted by an effective-medium rigidity percolation model. We present a simple model, based on capillary attraction, to explain the particle-size dependence of the threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
0
32
1
Order By: Relevance
“…Moreover, the few existing experimental studies have focused on very specific material e.g. particles in a clay dispersion [Coussot (1997), Ancey and Jorrot (2001)], a cement paste [Geiker et al (2002)], a foam [Cohen-Addad et al (2007)] or coal slurries [Sengun and Probstein (1989a,b)]. This poses a problem: can we use the results obtained in studies performed with noncolloidal particles in clay dispersions to predict the behavior of a mortar (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the few existing experimental studies have focused on very specific material e.g. particles in a clay dispersion [Coussot (1997), Ancey and Jorrot (2001)], a cement paste [Geiker et al (2002)], a foam [Cohen-Addad et al (2007)] or coal slurries [Sengun and Probstein (1989a,b)]. This poses a problem: can we use the results obtained in studies performed with noncolloidal particles in clay dispersions to predict the behavior of a mortar (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the surfactant adsorbs at the air/water interface causing effects such as Marangoni stresses and interfacial dilational elasticity which stabilize the foam. There have also been several recent examples of aqueous foams stabilized by partially hydrophobic particles 3–9. Such particles adsorb at the air/water interface and form a rigid shell (“armored bubbles”10) that protects bubbles against coalescence.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to previous work, our results highlight a critical size ratio below which a new elastic regime, characterized by unequaled modulus values as well as independence of size ratio, has been identified. This behavior, which has been clearly correlated to the formation of a thick granular skeleton of tightly packed particles, is not correctly described by the so-called rigidity percolation model [26]. We have shown that this increased elasticity originates from the strong synergistic effects that can be brought about in those particleloaded foams: the particles are small enough for forming an interstitial granular skeleton and the bubbles interface imposes a small but crucial confinement pressure on the packed particles, therefore providing significant mechanical strength to the granular skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, filling of molds requires an appropriate workability of the fresh foamy paste. In this regard, rheology of aqueous foams [7,23] and rheology of suspensions [24,25] have been studied mostly separately and only few recent studies have however tackled the issue of coupling of interstitial rheology and bubble elasticity in foams [9,26]. Whereas a satisfactory modeling of the global rheology is still lacking, unusual and interesting rheological behaviors have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation